Cultural Humility of Religious Communities and Well-Being in Sexual Minority Persons. Issue 3 (September 2019) - Mosher, David K.; McConnell, John M.; Hook, Joshua N.; Captari, Laura E.; Hodge, Adam; Dispenza, Franco; DeBlaere, Cirleen; Davis, Don E.; Van Tongeren, Daryl R.
Cultural humility has been shown to enhance cross-cultural relationships, but little research has explored how individuals perceive the cultural humility of a salient group. In the current study, we examined how perceptions of the cultural humility of a religious community affect the well-being of sexual minorities, who frequently experience discrimination, minority stress, and relational conflict in faith communities. As predicted, results indicated higher levels of perceived cultural humility in religious communities were associated with less depression, less anxiety, and more sense of belonging. Furthermore, minority stress mediated the relation between group cultural humility and depression, anxiety, and sense of belonging, even after controlling for the religious community's stance on LGB issues. We discuss our findings, limitations, and future directions for research, as well as offer practical applications for how cultural humility can benefit religious communities and sexual minorities.